Knowledge, attitude, and behaviour of Turkish dentists regarding contamination and prevention of Hepatitis B, Hepatitis C and HIV infection - Koseoglu, Merve; Toptan, Hande; Altindis, Selma (Universitas Padjadjaran, 2018)
Introduction: Dentists are at risk of Hepatitis B, Hepatitis C, and HIV infections in their professional practices. The purpose of this study was to determine the knowledge level, attitude, and behaviours of the Turkish dentists regarding contamination and prevention of Hepatitis B, Hepatitis C, and HIV infections. Methods: After receiving the required ethical and administrative approvals, a 33-item digital survey was applied within the context of the present study, and carried out amongst 58 dentists. Results: According to the results of this study, the knowledge level did not vary between different demographic features (p ˃ 0.05). However, the dentists’ attitude and behaviours were different. Post-exposure attitude towards Hepatitis B, Hepatitis C, and HIV infection did not vary between different demographic features (p ˃ 0.05). Female dentists who received education regarding infectious diseases more often got health check in case of injury (p ˂ 0.05). Female dentists felt more concerned than male dentists when they were treating infected patients, and they were more often using protective barriers (p ˂ 0.05). Dentists who were working at the university hospital and public hospital mostly had their Hepatitis B vaccinations more often than private clinics, also, dentists in university hospitals more often reported prefer to treat infected patients (p ˂ 0.05). Dentists who did not receive any education have reported that dental treatment of infected patients should be performed in specialised clinics (p ˂ 0.05). Conclusion: The Turkish dentists’ knowledge level, attitude, and behaviour were different. According to the findings of this study, efficacious education programs should be prepared for dentists to establish a positive attitude towards Hepatitis B, Hepatitis C, and HIV infected patients.Keywords: Dentists, Turkish, Hepatitis B virus, Hepatitis C virus, HIV.